Impact of COVID-19 on access to inputs for crop production in India: Assessment of disruption of COVID-19 farm input provision - Khartri-Chhetri, Arun; Sapkota, Tek Bahadur; Maharjan, Sofina (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Key messages - During the COVID-19 pandemic, farmers who were less dependent on the market for labor, machinery, fertilizer, and other inputs were less impacted than farmers who were more dependent on the supply of these inputs from the local market. - Many household characteristics and input management strategies have a significant role in minimizing the impact of the pandemic on crop production. - Reduction in inputs use such as fertilizer, irrigation, labor has a significant impact on crop yield and greenhouse gas (GHG) emissions. Emissions from the rice production were reduced with less fertilizer and irrigation use by many farmers in the study areas. - Addressing the disruption of pandemic conditions in farm input supply by government and private sector intervention and building resource base at household and community levels are two key strategies to manage current and future pandemic conditions.